ANALISIS KELAYAKAN PEMASARAN DAN KEUANGAN UMKM - Ali Imron (Fakultas Ekonomi Universitas Pekalongan, 2016)
This study aims to analyze the feasibility of Marketing and finance of UMKM in Pemalang. UMKM whichassessed the feasibility of marketing and processing of pineapple for the financial industry, the cultivation ofvegetables in the agropolitan waliksarimadu, organic rice cultivation, cultivation of mango arumanis, fish feedindustry, milk processing industry and fish meal as well as industrial brooms glagah. Marketing analysis is usedto focus more on segmentation, targeting and market positioning of each UMKM. Investment valuation analysisusing five methods of calculation of Total Value of Investment, Net Present Value (NPV), Internal Rate Of Return(IRR), Payback Period (PP) and the Benefit and Cost Ratio (BC). Based on the marketing and financial analysis itcan be concluded each UMKM feasible to develop its business.Keywords: marketing and financial feasibility of UMKM